2013
DOI: 10.5267/j.dsl.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Ranking fuzzy numbers using preference ratio: A utility function approach

Abstract: Ranking fuzzy numbers is one of the most important phases in any decision making process in fuzzy environments. In most cases, we deal with fuzzy numbers in the field of evaluating alternatives with fuzzy information or linguistic variables. This paper investigates ranking fuzzy numbers using the concept of preference ratio, introduces the weakness of this method, and proposes a new approach that overcomes the shortcoming of existing method. The proposed approach which is based on the concept of utility functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The review of techniques which have been developed for ranking of fuzzy numbers can be found in [32]. This study covers the analysis of the fuzzy ranking indices proposed before 1998 (among more recent works in this field, it is possible to distinguish, for instance, [35] [36]).…”
Section: Problems With Fuzzy Coefficientsmentioning
confidence: 99%
“…The review of techniques which have been developed for ranking of fuzzy numbers can be found in [32]. This study covers the analysis of the fuzzy ranking indices proposed before 1998 (among more recent works in this field, it is possible to distinguish, for instance, [35] [36]).…”
Section: Problems With Fuzzy Coefficientsmentioning
confidence: 99%
“…Ranking different alternatives has become one of the most important issues among decision makers and there are various studies associated with ranking industrial products (Sadi-Nezhad & Shahnazari-Shahrezaei, 2013). Technique of ranking by similarity by positive ideal solution (TOPSIS) is one of the most popular techniques for ranking various alternatives (Hwang & Yoon, 1981;Zaheri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%